2018
DOI: 10.1126/scisignal.aau0296
|View full text |Cite
|
Sign up to set email alerts
|

The LKB1–AMPK-α1 signaling pathway triggers hypoxic pulmonary vasoconstriction downstream of mitochondria

Abstract: Hypoxic pulmonary vasoconstriction (HPV), which aids ventilation-perfusion matching in the lungs, is triggered by mechanisms intrinsic to pulmonary arterial smooth muscles. The unique sensitivity of these muscles to hypoxia is conferred by mitochondrial cytochrome c oxidase subunit 4 isoform 2, the inhibition of which has been proposed to trigger HPV through increased generation of mitochondrial reactive oxygen species. Contrary to this model, we have shown that the LKB1–AMPK-α1 signaling pathway is critical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(64 citation statements)
references
References 60 publications
6
58
0
Order By: Relevance
“…It has been shown that activation of AMPK via increased AMP/ATP ratios primarily implies activation via LKB1. This conclusion is suggested by studies in mice with a hypomorphic expression of LKB1, which abrogated AMPK activation under hypoxia in smooth muscle cells, while a knockout of CaMKK2 had no effect on the activation of AMPK under hypoxia in mice [57]. In lung epithelial cells, only inhibition of LKB1, but no other upstream kinase, abrogated the activation of AMPK under hypoxia [42].…”
Section: Lkb1 Versus Camkk2mentioning
confidence: 98%
See 1 more Smart Citation
“…It has been shown that activation of AMPK via increased AMP/ATP ratios primarily implies activation via LKB1. This conclusion is suggested by studies in mice with a hypomorphic expression of LKB1, which abrogated AMPK activation under hypoxia in smooth muscle cells, while a knockout of CaMKK2 had no effect on the activation of AMPK under hypoxia in mice [57]. In lung epithelial cells, only inhibition of LKB1, but no other upstream kinase, abrogated the activation of AMPK under hypoxia [42].…”
Section: Lkb1 Versus Camkk2mentioning
confidence: 98%
“…While activation of AMPK under hypoxia has often been shown, it is still under discussion whether this activation is mediated by the hypoxic stimulus specifically [55,56] or if it is a side effect of the metabolic (and thus energetic) consequences inferred by hypoxia [47,57]. Also, if the former was true, how is the activation of AMPK mediated under hypoxia?…”
Section: Activation Of Ampk Under Hypoxiamentioning
confidence: 99%
“…It has been reported that SIRT3 can confer protection by regulating phosphorylation of AMPK, thereby inhibiting mTOR activity, which was paralleled by autophagy induction [38]. AMPK, with a critical role in lipophagy by initiation of chaperone-mediated autophagy and in governing cellular defenses against hypoxia, ischemia and oxidative stress [25,[39][40][41], serves as a regulator of cell survival or death. Given the well-documented positive role of AMPK activity in regulation of autophagy, we hypothesized that SIRT3 activates that AMPK-mTOR pathway and consequently induces autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…The initiation phase of acute HPV is primarily driven by smooth muscle constriction [ 41 ], with a threshold P O 2 ≈ 80 mmHg [ 24 ]. The cell-specific expression of atypical nuclear encoded subunits of the mitochondrial electron transport chain, such as COX4I2, may confer the acute sensitivity of these oxygen-sensing cells to physiological hypoxia [ 47 , 48 ], while increased expression, relative to systemic arteries, and activation of the AMP-activated protein kinase appears critical to induction of HPV downstream of mitochondria [ 49 , 50 ], including therein direct phosphorylation and inhibition of K V 1.5 channels that underpin the aforementioned IK V [ 50 , 51 ]. That is as it stands now, but we knew little of this back then.…”
Section: K N or Not K N Thatmentioning
confidence: 99%
“…Our further studies provided evidence that increased β-NADH formation under hypoxic conditions may facilitate cADPR formation from β-NAD + , by either augmenting ADP-ribosyl cyclase and/or inhibiting cADPR hydrolase activities [ 91 ]. Adding to this, later experiments suggested that cADPR accumulation and/or RyR activation by cADPR requires prior activation of AMPK, consequent to inhibition of mitochondrial oxidative phosphorylation during hypoxia [ 49 , 50 ]. Over and above this, the precise mechanism by which hypoxia promotes cADPR accumulation in pulmonary arterial smooth muscles remains to be confirmed.…”
Section: 8-bromo-cadpr and The Magical Mystery Tour Takes Offmentioning
confidence: 99%